How School Principals’ Managerial Skills Influences Teacher Self-Efficacy - Riswandi; Azizah, Alif Luthvi; Siagian, Nursalamah; Anwar, Sumarsih; Utami, Nur Ridha (Universitas Pendidikan Ganesha, 2024)
Teacher self-efficacy is an individual teacher's belief in his ability to manage, design and plan the activities needed to achieve educational goals. Teachers with high self-efficacy will provide many new ideas in their teaching. This study aimed to analyze the influences of school principals’ managerial skills on teacher self-efficacy, based on a quantitative research with the type of research ex-post facto. Data were collected using questionnaires with a Likert scale from 354 teachers in public elementary schools. The validity and reliability of the instrument were assessed, and the Pearson product moment correlation was used to examine the data. By first verifying normality, heteroscedasticity, multicollinearity, and linearity, the data collected was analyzed to find the direct correlation among variables. The study’s results showed that there was a positive and significant influence between the school principals’ managerial skills on teacher self-efficacy. The findings may be useful for developing countries seeking to improve teacher self-efficacy and the quality of their education. As suggested by the current research, ensuring teacher self-efficacy in teaching is crucial because of its positive impact on those with lower qualifications, ranks, and experience. The practical implication of this research is that the managerial skills of school principals can be improved continuously because it has been proven to increase teacher self-efficacy.